Labour market developments in Germany: Tales of decency and stability - Bea Ruoff (International Labour Organization (ILO), 2016)
Labour market developments in Germany can be separated into two major shocks: German reunification in the early 1990s, and the Hartz reforms in the early 2000s. In this paper it is argued that these two shocks divide the German wage bargaining system into the old labour market system, which is characterised by a high degree of coordination through pattern bargaining, and the new dual labour market system, where pattern bargaining exists to some extent but is characterized by a marked increase in precarious work. The consequences of these developments for the alleged "stable" and "decent" German labour market are outlined and policy proposals by the German Confederation of Trade Unions (DGB) to combat unnoticed (or condoned) dualism and its repercussions are discussed. It is argued that the DGB's claims are valid, but the list of proposals needs to be extended to include important features such as sufficient minimum wages, strengthened co-determination, and a stakeholder corporate governance system.
Keywords: 330; labour market analysis; unemployment; wage determination; precarious employment; trade union role; minimum wage; trend; Germany; German Democratic Republic; Germany; Federal Republic